2010
DOI: 10.2471/blt.08.060061
|View full text |Cite
|
Sign up to set email alerts
|

Multiple types of child maltreatment and adolescent mental health in Viet Nam

Abstract: Objective To examine the prevalence of multiple types of maltreatment (MTM), potentially confounding factors and associations with depression, anxiety and self-esteem among adolescents in Viet Nam. Methods In 2006 we conducted a cross-sectional survey of 2591 students (aged 12-18 years; 52.1% female) from randomlyselected classes in eight secondary schools in urban (Hanoi) and rural (Hai Duong) areas of northern Viet Nam (response rate, 94.7%). Sequential multiple regression analyses were performed to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 41 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…Our results also confirmed that frequent physical or emotional abuse from adults (parents or other adults in the family, teachers or other staff members at school) was an independent predictor of anxiety. This finding was similar to other recent studies in Ho Chi Minh City [ 12 ] in Hanoi and in rural Hai Duong [ 29 ]. This is also consistent with findings from other studies in Western countries that demonstrate that maltreatment in childhood predicted difficulties in psychological adjustment in adolescence [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results also confirmed that frequent physical or emotional abuse from adults (parents or other adults in the family, teachers or other staff members at school) was an independent predictor of anxiety. This finding was similar to other recent studies in Ho Chi Minh City [ 12 ] in Hanoi and in rural Hai Duong [ 29 ]. This is also consistent with findings from other studies in Western countries that demonstrate that maltreatment in childhood predicted difficulties in psychological adjustment in adolescence [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“… 7 In Vietnam, the prevalence of symptoms of mental disorders is high in adolescents. 31 , 32 This might explain the high prevalence of NSSI found in this study and indicate a need for intervention for both mental health symptoms and NSSI. Students with multiple mental health symptoms had a much greater likelihood of having engaged in NSSI and multiple methods of NSSI.…”
Section: Discussionmentioning
confidence: 77%
“…Yılmaz et al stated in a case study they conducted on an abuse case that child abuse was related to the socioeconomic level of the family (12). Nguyen et al Stated that in the United States of America, low socio-economic level and low parental education pose a risk for child abuse and neglect (13). Güler et al searched the socioeconomic structure of the family was shown among the important causes of child abuse and neglect, and they stated that economic difficulties may adversely affect the mother in terms of psychological aspects, considering that household needs and bud-get adjustments within the family are made especially by the mother.…”
Section: Discussionmentioning
confidence: 99%